Characterizing Ventilatory Muscle Dysfunction in Inclusion Body Myositis. (1st May 2023) - Brokamp, Gabrielle; Hurst, Lauren; Hartog, Leigh; Vilson, Ferdinand; Reynolds, Jerold; Elsheikh, Bakri H.; Arnold, W. David
Abstract : Objective: Investigation of the frequency and progression of ventilatory muscle dysfunction in patients with inclusion body myositis, the most common myopathy after age of 50 yrs. Prior research is limited to case series and cross-section studies. Design: This is a retrospective review of pulmonary function tests, respiratory symptoms, and muscle strength testing. Results: Of the 54 patients reviewed (mean age: 65 ± 9 yrs and disease duration: 7 ± 7 yrs), the majority ( n = 32, 59%) had restrictive forced vital capacity deficits at initial visit. Patients with reduced forced vital capacity showed higher prevalence of respiratory symptoms; but age, body mass index, and limb strength were similar when compared with patients without restrictive forced vital capacity. Mean rate of forced vital capacity decline of 0.108 l/yr in inclusion body myositis patients. Lower baseline limb strength correlated with longer disease duration and future forced vital capacity decline (eg, weaker patients experienced faster decline). Conclusions: Based on forced vital capacity, there is a high frequency of ventilatory pump muscle weakness in inclusion body myositis, which is associated with a higher burden of respiratory symptoms. Baseline strength may indicate risk of respiratory decline and need for vigilant screening. Importantly, ventilatory and limb muscle decline may not progress in a corresponding manner, highlighting the importance of pulmonary function surveillance.